Efektivitas Kebijakan Penatausahaan Pada Pengelolaan Barang Milik Negara Di Balai Pendidikan Dan Pelatihan Keagamaan Medan - Anthony Hardinal Sijabat; Rizkia Daulay (Balai Diklat Keagamaan Medan, 2021)
The research aims to describe the effectiveness policy at Balai Diklat Keagamaan Medan. The location of the research was conducted at Balai DIklat Keagamaan Medan, which is located at Jalan TB Simatupang No. 122 Medan. The problem raised in this research such as assets that move around the room without the knowledge of the manager of state property so that their whereabouts are not known which has an impact on assets management records that do not address real data in the field and state property managers who still have very minimal human resources and lack of human resources as users related to the administration of state property. This research uses qualitative research methods. It is used in a study to obtain a qualitative description and will be dominated by words, sentences, and descriptions and rarely uses numerical data. In discussing the existing problems, the writers use Campbell and Duncan’s theory of effectiveness. The result of the study shows that there are problems that make the policy of administering state property ineffective due to the lack of inventory implementation and the lack of resources for managing state-owned goods so that a better understanding of the policy of administering state-owned goods will have a significant impact on improving the administration of state-owned goods so that resulting in a more effective administration of state-owned goods.